Mirogabalin inhibits scratching behavior of spontaneous model mouse of atopic dermatitis - Matsuda, Kosuke; Kitano, Yutaka; Sawahata, Masahito; Kume, Toshiaki; Uta, Daisuke (Frontiers in Pharmacology, 2024)
Atopic dermatitis (AD) is one of the most prevalent intractable chronic itch diseases worldwide. In recent years, new molecular-targeted drugs have emerged, but side effects and economic challenges remain. Therefore, since it is important for AD patients to have a wider range of treatment options, it is important to explore new therapeutic agents. Gabapentinoids, gabapentin and pregabalin, have been shown to be effective for the clinical treatment of several chronic itch. Recently, mirogabalin (MGB) was developed as a novel gabapentinoid. MGB is a drug for neuropathic pain and has a margin of safety between its side effects and the analgesic effect for animal experiments. Herein, we showed that MGB exhibited an antipruritic effect in a mouse model of AD using NC/Nga mice. The oral administration of MGB (10 mg/kg) inhibited spontaneous scratching behavior in AD mice and its effect was dose dependently. Then, when MGB (10 mg/kg) was orally administrated to healthy mice, it did not affect motor function, including locomotor activity, wheel activity, and coordinated movement. Moreover, gabapentin (100 mg/kg) and pregabalin (30 mg/kg), inhibited spontaneous scratching behavior in AD mice and decreased motor function in healthy mice. Furthermore, intracisternal injection of MGB (10 μg/site) significantly suppressed spontaneous scratching behavior in AD mice. In summary, our results suggest that MGB exerts an antipruritic effect via the spinal dorsal horn using NC/Nga mice. We hope that MGB is a candidate for a novel therapeutic agent for AD with relatively few side effects.